Macroclimate at Different Altitudes on Changes in Microclimates in a Closed House - Wahyuningrum, H.; Mahfudz, L. D.; Muryani, R. (Jurnal Sain Peternakan Indonesia, 2022)
This study was conducted to determine and analyze the effect of differences in altitude levels on the macroclimate and microclimate in a closed house. This research was carried out at a closed house in the lowland, medium land, and highland with a length of 120 m and a width of 12 m. Observed data were made for 28 days at three times. Parameters observed include temperature, wind speed, humidity, and solar radiation. Macroclimate contribution to the microclimate was calculated based on the relationship's strength using correlation analysis and forming a regression equation. The results showed that the gift of macroclimate components to microclimate conditions in the form of temperature and humidity was more significant in the cages in the lowland and highland. In contrast, the contribution to wind speed was minimal. The predictor of air humidity in a cage in the lowland during the brooding phase was influenced by temperature, humidity, wind speed, and solar radiation; during the finisher phase, the temperature and humidity in the cage in the lowland were influenced by temperature, humidity, and solar radiation. This study concluded that the contribution of macroclimate factors to microclimate conditions in the brooding phase is more significant in the cage in the lowland. In comparison, in the finisher phase, the contribution is more important in the lowland and medium land.